2022
DOI: 10.31235/osf.io/u3whv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attitudes of learners at the Arabic Language Institute at King Abdulaziz University towards Online Collaborative Writing during Covid-19 Pandemic

Abstract: This study aims to examine learners’ attitudes at the Arabic Language Institute at King Abdulaziz University towards online collaborative writing during the Covid-19 Pandemic. The study was conducted in the first semester of the academic year 2021/2022. The study participants are students from the language Institute of King Abdul-Aziz University, Saudi Arabia. Forty-three students (19 males and 24 females) constituted the study population. The researcher administered a 30-item questionnaire. The results reveal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Deni and Zainal (2018) Padlet has proven effective in improving students' writing skills. Alwaleedi (2022) examined students' attitudes towards using Padlet for online collaborative writing activities at the Arabic Language Institute in Saudi Arabia. The results showed that students had an overall positive attitude, and demonstrated Padlet's ability to foster brainstorming, collaborative report writing, and overall writing competency through peer editing (Alwaleedi, 2022).…”
Section: Padlet As a Learning Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…Deni and Zainal (2018) Padlet has proven effective in improving students' writing skills. Alwaleedi (2022) examined students' attitudes towards using Padlet for online collaborative writing activities at the Arabic Language Institute in Saudi Arabia. The results showed that students had an overall positive attitude, and demonstrated Padlet's ability to foster brainstorming, collaborative report writing, and overall writing competency through peer editing (Alwaleedi, 2022).…”
Section: Padlet As a Learning Toolmentioning
confidence: 99%
“…Alwaleedi (2022) examined students' attitudes towards using Padlet for online collaborative writing activities at the Arabic Language Institute in Saudi Arabia. The results showed that students had an overall positive attitude, and demonstrated Padlet's ability to foster brainstorming, collaborative report writing, and overall writing competency through peer editing (Alwaleedi, 2022). Padlet's basic editing and plagiarism prevention tools, along with the option for public or private boards, ensure privacy and a conducive environment for online discussions (Simon & Fierro, 2023).…”
Section: Padlet As a Learning Toolmentioning
confidence: 99%
See 1 more Smart Citation